2019
DOI: 10.1186/s41235-019-0178-z
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effectiveness of two types of deceit detection training methods in older adults

Abstract: Background In general, people are poor at detecting deception. Older adults are even worse than young adults at detecting deceit, which might make them uniquely vulnerable to certain types of financial fraud. One reason for poor deceit detection abilities is that lay theories of cues to deception are not valid. This study compared the effectiveness of two training methods to improve deceit detection among older adults: valid facial cues versus valid verbal cues to deception. Approximately 150 olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…There were three central findings: (i) greater IAcc was associated with better lie detection; (ii) this effect strengthened with greater age among older adults; and (iii) greater IAcc was associated with better phishing email detection with increasing age in our older adult cohort. Integrating parallel lines of research on age and deception detection 14,15 and IAcc 24,25 , we provide evidence that greater IAcc enhances deception detection across the continuum of older adulthood, observed on two independent, naturalistic deception tasks (video-based lie telling and email-based phishing).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…There were three central findings: (i) greater IAcc was associated with better lie detection; (ii) this effect strengthened with greater age among older adults; and (iii) greater IAcc was associated with better phishing email detection with increasing age in our older adult cohort. Integrating parallel lines of research on age and deception detection 14,15 and IAcc 24,25 , we provide evidence that greater IAcc enhances deception detection across the continuum of older adulthood, observed on two independent, naturalistic deception tasks (video-based lie telling and email-based phishing).…”
Section: Discussionsupporting
confidence: 54%
“…Factors contributing to older adults' susceptibility to fraud include demographics, such as income and literacy 4 , as well as psychological factors such as depression 5 , age-related changes in the brain resulting in declining executive functioning and decision-making capacity [6][7][8][9] , and increased levels of trust [10][11][12][13] . In fact, compared to young adults, older adults are typically less accurate at detecting deception 14,15 and exhibit a greater truth bias, which is the tendency to believe others are telling the truth rather than lying 16,17 . These findings are in accordance with evidence that interpersonal trust increases across the adult lifespan 18,19 .…”
mentioning
confidence: 99%
“…As for the raw data provided by the iMotions platform on emotions, they were calculated to obtain a binary result with a threshold of 10, meaning that all those facial expressions that, with at least 10% probability, were rated as such by a human evaluator are given as valid (see Table 2 ). This criterion is the one used by e.g., Kjærstad et al ( 2020 ) and Stanley and Webster ( 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Statements judged with 60% accuracy were used because previous research has found that the veracity of written statements is judged at levels no better than chance (Masip et al, 2012) and therefore interventions to boost deception detection performance, such as training or measures to elicit cues, are required before group effects would be expected to emerge. Baseline detection rates were artificially increased to 60% so as to mimic the increase such successful interventions would have on performance (Colwell et al, 2012; De Turck et al, 1997; Porter et al, 2000; Stanley & Webster, 2019; Vrij, Evans, et al, 2004).…”
Section: Methodsmentioning
confidence: 99%